Indirect Rotor Field-Oriented Control of Fault-Tolerant Drive System for Three-Phase Induction Motor with Rotor Resistance Estimation Using EKF - Mohammad Jannati; N. R. N. Idris; M. J. A. Aziz (Institute of Advanced Engineering and Science, 2014)
The performance of an Indirect Rotor Field-Oriented Control (IRFOC) scheme for Induction Motors (IMs) is strongly dependent on the motor parameters especially, rotor resistance. As such, to ensure high performance drive system, the variation of the rotor resistance due to the temperature increase need to be estimated based on the available terminal variables. However, the algorithm used to estimate the rotor resistance for a balanced Three-Phase Induction Motor (TPIM) cannot be used for an open-phase fault IM; this is because the model of a faulty machine is different from the balanced 3-phase machine. In this paper, an IRFOC of fault-tolerant drive system (with stator open-phase fault) for a TPIM with rotor resistance estimation using Extended Kalman Filter (EKF) is proposed. The performance of the EKF based rotor resistance estimator is evaluated under different operating conditions using MATLAB simulation package. The proposed algorithm for estimation of rotor resistance in this paper can be applied to either balanced TPIM or Faulty TPIM (FTPIM). The simulation results showed that the proposed system is able to overcome the rotor resistance variations, load disturbance as well as stator open-phase fault condition, with good tracking capability.